Reducing Uncertainty in Idle Well Reactivation: A Novel Integrated Screening Framework for Mature Oil Fields - Sayoga Heru Prayitno; Hariyadi; Indah Widiyaningsih; Ndaru Cahyaningtyas; Mia Ferian Helmy; Bintang Pramuditha (Scientific Contributions Oil and Gas, 2026)
Mature oil fields are increasingly challenged by declining reservoir performance, resulting in a growing number of idle wells with remaining hydrocarbon potential. Despite their strategic importance, reactivation efforts are frequently constrained by high uncertainty in candidate selection due to fragmented evaluation practices, where production behaviour, well integrity, and reservoir quality are often assessed independently. This limitation often leads to suboptimal decision-making and unsuccessful reactivation programs.This study proposes an integrated screening framework to reduce uncertainty in idle well reactivation by systematically combining production diagnostics, well integrity evaluation, and reservoir characterization within a unified workflow.The proposed methodology integrates Water-Oil Ratio (WOR) trend analysis and WOR derivative analysis for water-production diagnostics, Cement Bond Log (CBL) interpretation for cement integrity and zonal isolation assessment, and petrophysical evaluation to determine reservoir quality and hydrocarbon potential. These parameters are incorporated into structured screening criteria to enable consistent classification of reactivation potential. The framework was applied to Well BP-16 in an Indonesian mature oil field as a representative case study. The results indicate that excessive water production and poor cement bonding are the dominant factors contributing to well inactivity. The integrated evaluation also identified a previously overlooked interval at 693–696 m with favourable reservoir properties and lower water-production risk.Compared with conventional single-domain evaluations, the proposed approach provides a more comprehensive understanding of subsurface conditions by linking production behaviour, well integrity, and reservoir characteristics within a single evaluation framework. This integration improves the reliability of reactivation candidate selection and supports more effective reactivation planning. The proposed framework offers a practical and field-applicable approach for optimizing idle well utilization, improving production efficiency, and extending the economic life of mature oil fields.